Cloning and characterization of the glutamate dehydrogenase gene in Streptococcus bovis. (23rd November 2016) - Ando, Tasuke; Sugawara, Yoko; Nishio, Ryohei; Murakami, Miho; Isogai, Emiko; Yoneyama, Hiroshi
Abstract: Streptococcus bovis, an etiologic agent of rumen acidosis in cattle, is a rumen bacterium that can grow in a chemically defined medium containing ammonia as a sole source of nitrogen. To understand its ability to assimilate inorganic ammonia, we focused on the function of glutamate dehydrogenase. In order to identify the gene encoding this enzyme, we first amplified an internal region of the gene by using degenerate primers corresponding to hexameric family I and NAD(P) + binding motifs. Subsequently, inverse PCR was used to identify the whole gene, comprising an open reading frame of 1350 bp that encodes 449 amino acid residues that appear to have the substrate binding site of glutamate dehydrogenase observed in other organisms. Upon introduction of a recombinant plasmid harboring the gene into an Escherichia coli glutamate auxotroph lacking glutamate dehydrogenase and glutamate synthase, the transformants gained the ability to grow on minimal medium without glutamate supplementation. When cell extracts of the transformant were resolved by blue native polyacrylamide gel electrophoresis followed by activity staining, a single protein band appeared that corresponded to the size of S. bovis glutamate dehydrogenase. Based on these results, we concluded that the gene obtained encodes glutamate dehydrogenase in S. bovis .